1980
DOI: 10.1111/j.1745-4557.1980.tb00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg Quality as Affected by Storage and Handling Methods

Abstract: The quality and shelf-life o f fresh eggs were studied under simulated climatic conditions as found in Kuwait. Three groups of eggs (unwashed, washed, and washed and oil treated) were used. The treated eggs were stored at 5", 25", 37" and 42°C. Internal and external quality and sensory evaluation o f the eggs stored up to 7 5 days were determined. The quality of the unwashed and washed eggs stored at 37°C and 42°C deteriorated rapidly while the wash and oil treatment extended shelf-life but decreased in qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 3 publications
5
22
1
Order By: Relevance
“…On the other hand, the Haugh unit (38.16) of CH-coated eggs after 4 weeks of storage was comparable to that (37.00) of noncoated eggs after 2 weeks of storage; this implies that CH coating was also effective in preserving the albumen quality of eggs for at least two more weeks compared with noncoated eggs at 25°C. These results were substantiated by previous observations for MOcoated eggs (Homler & Stadelman, 1963;Kamel et al, 1980;Waimaleongora-Ek et al, 2009) and CH-coated eggs (Lee et al, 1996;Bhale et al, 2003;Kim et al, 2007Kim et al, , 2008.…”
Section: Effects Of Mineral Oil Chitosan Solution and Their Emulsionsupporting
confidence: 94%
“…On the other hand, the Haugh unit (38.16) of CH-coated eggs after 4 weeks of storage was comparable to that (37.00) of noncoated eggs after 2 weeks of storage; this implies that CH coating was also effective in preserving the albumen quality of eggs for at least two more weeks compared with noncoated eggs at 25°C. These results were substantiated by previous observations for MOcoated eggs (Homler & Stadelman, 1963;Kamel et al, 1980;Waimaleongora-Ek et al, 2009) and CH-coated eggs (Lee et al, 1996;Bhale et al, 2003;Kim et al, 2007Kim et al, , 2008.…”
Section: Effects Of Mineral Oil Chitosan Solution and Their Emulsionsupporting
confidence: 94%
“…This indicated that during the first 5 wk of storage, refrigeration alone was not sufficient to keep the weight loss below the FAO's recommended level whereas the MO or MO:CH coating without refrigeration was. Kamel and others (1980) also reported that eggs coated with MO and stored at 25 °C showed a lower weight loss compared with that of noncoated eggs stored at 5 °C after the same storage period of 40 d (0.6% against 2.3%). This study demonstrated that MO and MO:CH emulsion (irrespective of emulsifier types) coatings can equally ( P > 0.05) offer a protective barrier against the transfer of moisture through the eggshell, thus minimizing weight loss for at least 5 wk at 25 °C (<1.20%, Table 1) and, in a synergistic effect with refrigeration, at least 20 wk at 4 °C (<1.63%, Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…Differences in initial egg size, quality, and storage conditions (temperature and period) may affect albumen pH before and after storage (Goodwin, Wilson, & Stadelman, 1962). Kamel, Bond, and Diab (1980) stated that the albumen pH of noncoated eggs increased from the initial value of 8.64 to 9.29 and 9.51 at 5 C and 25 C, respectively, after 33 days of storage.…”
Section: Tablementioning
confidence: 98%